(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
I do not intend to elaborate the subject of biological monitoring of the state of the environment (bioindicators) in this chapter. I would rather restrict the subject to basic concepts of environmental monitoring. As a result of population growth, rapid industrial and technological development, urbanisation and unjudicious planning without due regard to sustainable development, there have been induced a variety of changes iii the environment. Human activities induce such changes in the environment in the form of pollution and perturbation that cause widespread damage to the living organisms in the biosphere The result is the disruption of ecological balance, a growing threat to the entire life support system which is rapidly lacing extinction.